2019
DOI: 10.4314/jae.v23i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Agricultural Counselling Centre in the Development of Black Rice Programme in Central Java, Indonesia

Abstract: The study assessed the role of agricultural counselling centres in the development of black rice programme in Central Java, Indonesia. Black rice is a food source that has health benefits. Purplish black colour comes from anthocyanin which contains high antioxidants, used as an alternative healthy food to prevent degenerative diseases such as heart attacks and diabetes. The purpose of the study was to analyse the convergence communication and communication networks of actors who are involved in the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Sadono, (2009) argues that there has been a shift in the pattern of communication in agricultural development from a linear nature (from the government to farmers) towards a participatory and dialogic communication pattern so that it can fulfill the aspirations of farmers. In the case of the black rice development program, it was found that communication patterns tended to use personal network communication patterns (Zulfiningrum, Sumardjo, Saleh, & Agusta, 2019). The communication factor becomes an important factor in institutional management in information processing.…”
mentioning
confidence: 99%
“…Sadono, (2009) argues that there has been a shift in the pattern of communication in agricultural development from a linear nature (from the government to farmers) towards a participatory and dialogic communication pattern so that it can fulfill the aspirations of farmers. In the case of the black rice development program, it was found that communication patterns tended to use personal network communication patterns (Zulfiningrum, Sumardjo, Saleh, & Agusta, 2019). The communication factor becomes an important factor in institutional management in information processing.…”
mentioning
confidence: 99%